Implementasi Motivasi Model ARCS (Attention, Relevance, Confidence, and Satisfaction) dalam Pembelajaran Pendidikan Agama Kristen - Lidia Susanti; Carla Imbiri (Sekolah Tinggi Teologi Intheos Surakarta, 2020)
Abstract. The purpose of this study was to describe the effectiveness of learning using ARCS motivation in Christian Religious Education subjects 1st grade of the elementary school. The design used in this study was a quasi experimental design and nonequivalent control group design method with 57 research subjects in 1st grade of Charis Christian Elementary School. Learning models with ARCS motivation design as independent variables and learning outcomes as dependent variables. Through testing the difference between independent samples T-Test between the control class and the experimental class (ARCS), it was proved that there were significant differences in learning outcomes between the experimental class and the control class t (57) = 4,050; p <0.05. Based on the results of the independent sample T-Test analysis, a significant value (Sig. (2 tailed) = 0.000) was obtained between the experimental class and the control class. From the results of this study it could be concluded that the implementation of ARCS motivation design can significantly improve learning outcomes in Christian Religious Education subjects in 1st grade of the elementary school.Abstrak. Tujuan penelitian ini untuk memberikan gambaran efektivitas pembelajaran menggunakan motivasi ARCS pada mata pelajaran Pendidikan Agama Kristen di kelas 1 SD. Rancangan penelitian ini menggunakan quasi experimental design metode nonequivalent control group design dengan subyek penelitian 57 siswa kelas 1 SD Kristen Charis. Model pembelajaran dengan desain motivasi ARCS sebagai variabel bebas dan hasil belajar sebagai variabel terikat. Melalui uji perbedaan independent samples T-Test antara kelas kontrol dan kelas eksperimen (ARCS), terbukti ada perbedaan pada hasil belajar yang signifikan antara kelompok kelas eksperimen dan kelas kontrol t(57) = 4,050; p<0.05. Berdasarkan hasil analisa independent sample T-Test, diperoleh nilai yang signifikan (Sig.(2 tailed)=0.000) antara kelas eksperimen dan kelas kontrol. Dari hasil penelitian ini dapat disimpulkan bahwa penerapan desain motivasi ARCS dapat secara signifikan meningkatkan hasil belajar pada mata pelajaran PAK di kelas 1 SD.